2017
DOI: 10.4103/jisppd.jisppd_152_16
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to dental care for children with special needs: General dentists' perception in Kerala, India

Abstract: Greatest barriers as perceived by the practitioners were their level of training and lack of motivation of caretakers. Significant association was found between experience of the dentist with the frequency with which they reported seeing children with special needs (pConclusion: Findings from this study provide a valid picture of barriers to access for children with special needs within general dental private practice system. Recommendations for amendment of undergraduate dental curriculum is made in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 0 publications
2
7
0
1
Order By: Relevance
“…Majority of the practising dentists (83.7%) conveyed inadequate training as a barrier in managing these children at their private dental clinics. These findings were in congruence with a study reported by Adhyanthaya et al (2017) who stated that 84.6% of dentists felt a similar lack of training.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Majority of the practising dentists (83.7%) conveyed inadequate training as a barrier in managing these children at their private dental clinics. These findings were in congruence with a study reported by Adhyanthaya et al (2017) who stated that 84.6% of dentists felt a similar lack of training.…”
Section: Discussionsupporting
confidence: 92%
“…Around 43.8% of dentists were comfortable in delivering preventive treatments to children with disability, which concurred with findings by Adhyanthaya et al (2017) who mentioned that 30.8% of dentists gave only oral health education and preventive treatment to these clients. The study also reported that dentists had difficulty in gaining access to their mouths.…”
Section: Discussionsupporting
confidence: 83%
“…A diferencia de los factores planteados en esta investigación, Casamassimo et al (29) refieren que los factores que aumentan la probabilidad de la atención a PCD son las experiencias educativas prácticas en las escuelas de odontología sobre la atención, los cono-cimientos y una alta preparación. Sin embargo, al corroborar los resultados arrojados por esta investigación, Adyanthaya et al (30) coinciden en que los odontólogos que tenían experiencia práctica de más de 5 años encontraron barreras con mayor frecuencia, y esto fue estadísticamente significativo (P = 0.01).…”
Section: Discussionunclassified
“… 6 Their ability to physically access the dental clinics and offices, along with their ability to afford the cost of the treatment and inadequate financing for dental treatment, may hinder their access to dental clinics. 6 , 9 12 Moreover, the preparedness and willingness of dental care providers to treat patients with special needs may impact access and thus their oral health. 1 , 3 , 13 …”
Section: Literature Reviewmentioning
confidence: 99%